Most mRNAs in the nematode Ascaris lumbricoides are trans-spliced: a role for spliced leader addition in translational efficiency. - Maroney, P A (1995)
Some pre-mRNAs in nematodes are processed by trans-splicing. In this reaction, a 22-nt 5' terminal exon (the spliced leader, SL) and its associated 2,2,7-trimethylguanosine cap are acquired from a specialized Sm snRNP, the SL RNP. Although it has been evident for many years that not all nematode mRNAs contain the SL sequence, the prevalence of trans-spliced mRNAs has, with the exception of Caenorhabditis elegans, not been determined. To address this question in an organism amenable to biochemical analysis, we have prepared a message-dependent protein synthesis system from developing embryos of the parasitic nematode, Ascaris lumbricoides. Using this system, we have used both hybrid-arrest and hybrid-selection approaches to show that the vast majority (80-90%) of A. lumbricoides mRNAs contain the SL sequence and therefore are processed by trans-splicing. Furthermore, to examine the effect of SL addition on translation, we have measured levels of protein synthesis in extracts programmed with a variety of synthetic mRNAs. We find that the SL sequence itself and its associated hypermethylated cap functionally collaborate to enhance translational efficiency, presumably at the level of initiation of protein synthesis. These results indicate that trans-splicing plays a larger role in nematode gene expression than previously suspected.